Tractor’s engine efficiency and exhaust emissions’ research in drilling work - Juostas, Antanas; Janulevičius, Algirdas (Journal of Environmental Engineering and Landscape Management, 2014)
Tis paper provides an overview of possibilities for determining tractor’s engine load, fuel consumption and exhaust emissions in real operating conditions. Theuse of accumulated database in tractor’s electronic control modules for the analysis of engine load, fuel consumption and exhaust emissions is analysed. The methodology for analysis of engine power, speed and exhaust emissions’ dependencies, also for analysis of engine exhaust emissions is presented. Tis paper presents testing results of the unit combined of tractor “Massey Ferguson MF 6499” and drilling machine “Vaderstad Rapid” by engine load, fuel consumption and exhaust emissions. Drilling process time, engine load, fuel consumption and exhaust emission components’ distribution are presented in different engine speed and cyclic fuel injection modes. Test results are analysed separately for technological drilling and work processes at the headland. In the technological process of drilling, if the tractor engine speed and, correspondingly, the transmission gear ratio were reduced to get the set working speed, fuel consumption decreased, CO and CO2 emissions varied slightly, but the NOx increased significantly. Significant part of exhaust emissions occurred at headlands. The conclusion is that the fuel consumption and exhaust emissions, including harmful components, can be reduced only by complex optimization of technological processes and tractor operating modes. First published online: 19 Mar 2014